Nghiên cứu thiết kế, chế tạo hệ thống giám sát và phân loại các động cơ điện ứng dụng công nghệ xử lý ảnh - Huỳnh Phạm Chí Khoa (2025)
Nghiên cứu thiết kế, chế tạo hệ thống giám sát và phân loại các động cơ điện ứng dụng công nghệ xử lý ảnh